Synthesis of biodiesel in continuous flow packed with ion exchange kenaf fiber - Zabaruddin, Nur Haryani (2020)
Biodiesel has become increasingly attractive to be explore further for its environmental benefits such as renewable, bio-degradable, non-flammable, non-toxic, and sulfur-free. The most common biodiesel technologies employ homogenous catalysts to induce the reaction between alcohol and the triglycerides during transesterification. Although the transesterification reaction of triglycerides with alcohols using homogeneous catalyst is well known and practiced on a commercial scale, there is plenty of scope to improve this process. There is an approach that involves the use of heterogeneous catalysts that could be packed in a packed-bed reactor, and this would enable a continuous process to be developed. Recent progresses in the development of heterogeneous catalysts have been the generation of ion exchanger to improve transesterification. Previous studies have reported the application of anion exchange catalyst that derived from synthetic materials for production of biodiesel. However, removal of spent catalyst is a problem as it falls under the category of non-biodegradable wastes. The discovery of a novel low cost and environment friendly catalyst is an attractive option for their utilization and safe disposal. This study aims to investigate the use of kenaf fiber in the preparation of anion exchange catalyst used in transesterification. The fabrication of an anion exchange kenaf catalyst involved three steps: delignification of kenaf fiber, pre-irradiation induced emulsion graft polymerization of kenaf fiber and quaternary amination. The objective of this work was to develop a continuous system using an anion exchange kenaf catalyst and to evaluate the performance of this plant-based catalyst to produce biodiesel in a packed bed reactor. The transesterification of refined palm oil with ethanol in the presence of a ananion exchange kenaf catalyst was carried out. A single tubular flow reactors system in the concurrent up-flow configuration was built in the laboratory scale.The effect of the process parameters such as molar ratio ethanol to refined palm oil, packed bed height and volumetric flow rate on the triglycerides conversion and FAEE (fatty acid ethyl ester) yields were investigated. Screening design using full factorial were conducted to find the important factors and to identify the optimum range of the yield. The optimum range was between 95 - 97% conversion within a reaction ethanol to oil ratio 40:1 - 60:1, packed bed height of 4 cm – 12 cm and volumetric flow rate of 0.3 - 0.5 mL min-1. The response surface methodology (RSM) based on the central composite design (CCD) was used to optimize the process. The optimization were conducted around the optimum range established by the full factorial design. The optimum conditions for transesterification of refined palm oil to fatty acid ethyl ester were obtained at 9.81 cm packed bed height, 50:1 ethanol to oil molar ratio and volumetric flow rate of 0.38 ml min-1. At these optimum conditions, the FAEE yield was 96.74 %, which is well within the yield of 97.29 % as predicted by the model. Although it was shown that high conversions can be achieved over extended time on stream, it was clear that the catalyst was losing its activity. Measurements also showed that during a regeneration experiment, kenaf fiber was dissolved in the solvent and leaching of the catalyst active sites which resulted in poor catalyst reusability. Based on the results obtained, anion exchange kenaf catalyst exhibited good performance for the transesterification of refined palm oil with ethanol to produce FAEEs in packed bed reactors.